Book Review Buckley, R. (2011) Debt-for-Development Exchanges: History and New Applications - Lee C. Moerman (Australasian Accounting, Business and Finance Journal, 2012)
Books and articles highlighting intractable debt, poverty and development abound in both the academic and popular literature. This addition to the debate is both timely and interesting as it subsumes the economic debate to the broader social, political, environmental and institutional context of debt in developing countries. Debt-for-Development Exchanges: History and New Applications is intended for a wide audience including: academics from a range of disciplines (including accounting and finance); non-Government organisations (NGOs); civil society groups; and, both debtor and creditor governments and public sector organisations.
Keywords: debt-for-development; Third World Debt; illegitimate debt; Jubilee; book review